Comprehensive Roles and Future Perspectives of Exosomes in Peritoneal Metastasis of Gastric Cancer - Chen, Xiangliu; Wang, Haiyong; Huang, Yingying; Chen, Yanyan; Chen, Chuanzhi; Zhuo, Wei; Teng, Lisong (Frontiers in Oncology, 2021)
Gastric cancer is one of the most prevalent digestive malignancies. A great number of gastric cancer patients who were in their first visit or underwent curative resection are diagnosed with widespread meta-static niche within the peritoneal cavity. Overwhelming evidence has demonstrated that exosomes, a variety of biologically functional extracellular vesicles composed of a massive active factors, mediate progression and metastasis of gastric cancer. Although the regulatory mechanism of exosomes remain fairly elusive，they are responsible for intercellular communication between tumor cells and normal stroma, cancer-related fibroblasts, immune cells within the primary tumor and metastatic niche. In this review, we provide new insights into the molecular signatures of gastric cancer-associated exosomes in reprogramming the tumor microenvironment, and the subsequent promotion of peritoneal metastasis, including infiltrating gastric wall, implanting into the pre-metastatic peritoneum of tumor cells and remodeling pre-metastatic niche. Based on this review, We hope to draw a more general conclusion for the functions of exosomes in the progression and peritoneal metastasis of gastric cancer and highlight the future perspective on strategies targeting exosomes in prognostic biomarkers and therapy for peritoneal metastasis.